Effect of irrigation efficiency enhancement on water demand of date palms in a Tunisian oasis under climate change - Zied Haj-Amor (IWA Publishing, 2021)
Consideration of future change in water salinity is important for estimating irrigation demand in salinity-prone arid regions. Further, it is important to evaluate the contribution of irrigation efficiency enhancement to climate change resilience. Based on field measurements in 2019, a simulation approach from 2019 to 2050 was carried out in this study to investigate the impact of climate change and its consequences (i.e., change in water salinity) on the future gross irrigation demand of date palms and possible applied dose of water in a Tunisian oasis considering different irrigation efficiency enhancements. The estimation was done under very high (RCP 8.5), medium (RCP 6.0), and low (RCP 4.5) emission scenarios using the CROPWAT model. Results first showed an increase in gross irrigation requirement under inefficient surface irrigation (37% efficiency) from 3,340 mm year−1 in 2019 to 3,588–3,642 mm year−1 in 2050 for different climate change scenarios. This significant increase is mainly attributed to a significant change in climate variables and a high increase in water salinity. Second, considerable water savings (up to 1,980 mm) can be achieved if surface irrigation efficiency increases from the current value of 37–70%. Finally, much water can be saved only by reducing the overdose amount of water. HIGHLIGHTS Takes into consideration future change in applied water salinity and potential contribution of irrigation efficiency enhancement to climate change resilience.; Investigates the effect of three climate change scenarios (RCP 8.5: very high emission scenario, RCP 6.0: medium emission scenario and RCP 4.5: lowest emission scenario) and its consequences (i.e. change in water salinity) on future gross irrigation demand (GIR) of date palms.;